2009
DOI: 10.2215/cjn.00570109
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Treatment of Adult Patients with Steroid-Resistant Focal Segmental Glomerulosclerosis

Abstract: Background and objectives: Isolated case reports have shown a beneficial effect of rituximab on pediatric patients with primary FSGS, but there is no information about rituximab treatment of FSGS in adults.Design, setting, participants, & measurements: All patients who had biopsy-proven FSGS and were treated with rituximab in Spain were identified, independent of their positive or negative response, among the nephrology departments that belong to the Spanish Group for the Study of Glomerular Diseases (GLOSEN).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 27 publications
2
81
0
2
Order By: Relevance
“…FSGS is more common in the adult population and can be a challenge not only in the native kidney, but as recurrent disease in the renal allograft. The use of RTX in primary FSGS in adults has had variable, but mostly negative results in small case series [90], [91] and [92]. However, it may be useful in treating posttransplant relapse [93], [94] and [95].…”
Section: Focal Segmental Glomerulosclerosis and Minimal Change Diseasementioning
confidence: 99%
“…FSGS is more common in the adult population and can be a challenge not only in the native kidney, but as recurrent disease in the renal allograft. The use of RTX in primary FSGS in adults has had variable, but mostly negative results in small case series [90], [91] and [92]. However, it may be useful in treating posttransplant relapse [93], [94] and [95].…”
Section: Focal Segmental Glomerulosclerosis and Minimal Change Diseasementioning
confidence: 99%
“…9,10 Furthermore, recent reports suggest that rituximab, a mAb to CD20 that depletes mature B cells, may be beneficial in some patients with the nephrotic syndrome. [11][12][13][14][15][16] However, the mechanisms by which rituximab alleviates the nephrotic syndrome are not yet known. Recent work has demonstrated that "natural antibody" contributes to tissue injury in a number of different diseases.…”
mentioning
confidence: 99%
“…[30][31][32][33][34] On the contrary, Spanish Group for the Study of Glomerular Diseases (GLOSEN) reported that rituximab was successful in improving renal function and achieving a sustained reduction in proteinuria in two of eight adult patients with FSGS. 35 No differences were observed in CD20 + B lymphocyte count among the responder and non-responders. It is therefore plausible that rituximab may induce anti-proteinuric effect through mechanisms independent of B-cell depletion.…”
Section: Rituximab In Glomerular Diseasesmentioning
confidence: 90%